Chemical characteristics and source apportionment of particulate matter (PM2.5) in Dammam, Saudi Arabia: Impact of dust storms - Alwadei, Manna; Srivastava, Deepchandra; Alam, Mohammed S.; Shi, Zongbo; Bloss, William J. (Atmospheric Environment: X, 2022)
Atmospheric particulate matter (PM) is known to be harmful to human and environmental health, with factors including particle size and composition thought to be key drivers of toxicity. Understanding the composition and hence sources of PM is critical to distinguish between anthropogenic and natural impacts, and develop the most efficient air pollution mitigation policies. This distinction is particularly important in areas affected by dust storm activity from nearby arid regions, which may dominate long-term PM mass concentrations. In this work, 24-hour PM2.5 samples were collected from two locations in Dammam city, Saudi Arabia during the winter and summer of 2018, and subjected to detailed analysis to assess the PM characteristics and sources. Offline chemical analysis of the samples utilied ICP/MS, ion chromatography and thermal decomposition for measurement of trace metals, ions and OC/EC concentrations, respectively. Positive Matrix Factorization (PMF) analyses were used to identify sources of PM2.5 in Dammam. The mean PM2.5 mass concentration in the summer was twice that in the winter at both locations, and crustal and secondary inorganic aerosol components dominated over other species in determining PM2.5 mass concentrations at both seasons and locations. The PMF analysis identified six source factors, including crustal, nitrate-rich, sea salt, sulfate-rich, biomass burning and traffic sources. In addition, the impact of dust storms on PM2.5 concentrations was analysed. Dust storms increased the 24-hour average concentration of PM2.5 by three-fold, and that of crustal elements by five-fold while the impact of dust storms on components identified as anthropogenic in origin was limited. Overall, dust-storm activity accounted for 42% of PM2.5 mass concentration; after accounting for this aspect, secondary inorganic components derived largely from primary pollutant emissions dominated the remaining PM2.5 mass. •Comprehensive assessment of PM2.5 composition and sources in Dammam, Saudi Arabia.•Average 24-hour PM2.5 mass concentrations ranged from 54 to 121 ug/m3.•Dominant components found to be crustal elements, metals, organic and inorganic carbon.•Anthropogenic sources accounted for 40% of PM2.5 mass, rising to 58% if dust storm periods were excluded.•These results highlight emissions control priorities to improve air quality in Saudi Arabia.